Computer Simulation of Adsorption of C60 Fullerene Molecule on Reconstructed Si(100) Surface - Urolov, Ikrom Z.; Umarov, Farid F.; Yadgarov, Ishmumin D.; Rakhmanov, Ganiboy T.; Jabborov, Khayitmurod I. (East European Journal of Physics, 2024)
The adsorption of the C60 fullerene molecule has been studied in various configurations on a reconstructed Si(100) silicon surface. Among fullerenes, fullerene C60 is of particular importance since it has the most stable form and consists of 60 carbon atoms. Monocrystalline silicon has the diamond structure, the size of its crystal lattice is 5.43 Å. The MD-simulation calculations have been performed using the open source LAMMPS MD-simulator software package and the Nanotube Modeler computer program. The Tersoff interatomic potential has been used to determine the interactions between the Si-Si, C-C and Si-C atoms. The adsorption energy of the C60 molecule on the reconstructed Si(100) surface, the bond lengths and the number of bonds formed depend on the adsorption geometry, i.e. at what point on the substrate the molecule is adsorbed and in what configuration.